Post mortem genetic determination of age and sex of unidentifiable remains admitted to the Pretoria Medico-Legal Laboratory - Van Niekerk, Chantal (University of Pretoria, 2022)
Dissertation (MSc (Medical Criminalistics))--University of Pretoria, 2021.